Developing a scale to assess Islamic values application in quality management: a study among Malaysian organisations / Amal Hayati Ishak - Ishak, Amal Hayati (Institute of Graduate Studies, UiTM, 2016)
Quality management has long been established at the advent of Industrial Revolution. Since then, the widespread of quality management across the globe has been owed to the Western and Japanese quality gurus. Despite overwhelming influence of both cultures, contemporary scholars have consistently discussed Islamic perspectives of quality management since the 1990s. Their discussion is enlightened with primary sources of Islam, reflecting a plethora of Islamic values embedded in quality management practice. In parallel, a Malaysian national-level standard, the MS1900 or the Shariah-based Quality Management System has been established, aiming towards internalization of Islamic values. The standard initiates the ‘Organisational Values’ clause which requires organisations to apply, monitor and measure values application. Although MS1900 emphasizes on Islamic values measurement, existing scales used by organisations are self-developed and unstandardized. Yet, their validity information is ambiguous. Though the MRPI (Muslim Religiosity Personality Inventory) and IWE (Islamic Work Ethics) scale measure Islamic values, they apply for individual-level measurement and not focused on quality management. Moreover, literature-based scales are built on Western theoretical framework without due reference to Islamic substance. They are also being validated in the Western ambience. Such scales do not match the MS1900 aspirations…